1999
DOI: 10.3354/dao036163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary β-1,3-glucan on resistance to white spot syndrome virus (WSSV) in postlarval and juvenile Penaeus monodon

Abstract: This study evaluated the effectiveness of dietary incorporation of P-1,3-glucan from SchizophyUum commune in enhancing the resistance of postlarval (PL15) or juvenile (5.5 * 0.5 g ) Penaeus monodon to white spot syndron~e virus (WSSV). The shrimp were fed experimental diets with (2 g kg-' diet) or without P-1,3-glucan for 15 d (postlarvae) or 10 or 20 d (juveniles). Following these dietary treatments, the postlarvae were challenged by imrnerslon and the juveniles by injection using WSSV solution. After challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 14 publications
2
50
0
Order By: Relevance
“…Haemocytes are responsible for clotting, exoskeleton hardening and elimination of foreign materials [27]. Mean THCs of healthy penaeid shrimps ranged from 20 to 40 Â 10 6 cells ml ÿ1 [20]. Molting, development of organs, reproductive status, nutritional condition and disease have been shown to influence haemocyte abundance [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haemocytes are responsible for clotting, exoskeleton hardening and elimination of foreign materials [27]. Mean THCs of healthy penaeid shrimps ranged from 20 to 40 Â 10 6 cells ml ÿ1 [20]. Molting, development of organs, reproductive status, nutritional condition and disease have been shown to influence haemocyte abundance [29].…”
Section: Discussionmentioning
confidence: 99%
“…The DNA extraction and PCR amplification followed the method described by Chang et al [20]. Different organs such as head tissue, eye stalk, gills and tail muscle of experimental and control shrimps (AeE) were tested by first step PCR.…”
Section: Molecular Diagnosis Of Wssvmentioning
confidence: 99%
“…The most active of these compounds is (1-3)-β-D-glucan (Bhon and Be Miller, 1995), a natural polymer isolated from the cell wall of yeast and mold. β-glucans have been used as immunostimulants to enhance the defence potential of fish and shellfish against bacterial or viral infection (Oliver et al, 1986;Sung et al, 1994;Song et al, 1997;Chang et al, 1999Chang et al, , 2000Chang et al, , 2003. Currently many commercial immunostimulants are available in the shrimp aquaculture industry and are extensively used by shrimp farmers.…”
Section: Introductionmentioning
confidence: 99%
“…A low level of protection against WSSV challenge was observed in the control shrimp that were orally vaccinated with E. coli proteins, with a 54% RPS following oral WSSV challenge and 22% by immersion challenge (Table 3). We believe this low level of WSSV protection suggests that the E. coli proteins might have an immunostimulatory effect on the shrimp as in previous studies , Chen et al 1999, Sritunyalucksana et al 1999. Wu et al (2002) reported that resistance to WSSV in shrimp that survived WSD appeared 3 wk after primary infection and persisted for about 2 mo.…”
mentioning
confidence: 88%